VD_FINDINFO Jug / 2023 / 79 vom 12. Mai 2022 - VD Tribunal cantonal (2022)
DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, ÉMEUTE, VIOLENCE CONTRE LES AUTORITÉS | 144 al. 1 CP, 260 CP, 285 ch. 2 CP, 35 DPMin, 36 al. 1 let. c DPMin, 44 PPMin